2019
DOI: 10.1186/s12889-019-6642-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in a rural community in South Africa: what they know, what they think they know and what they recommend

Abstract: BackgroundHypertension is one of the most important risk factors for cardiovascular disease and has a high prevalence in South Africa and other low- and middle-income countries. However, awareness of hypertension has been reported to be low. Health programmes can increase awareness of hypertension and its causes, but hinge on the knowledge and perception of the targeted community. Therefore, this study investigated knowledge on and perceptions about hypertension of community members in a rural area in Limpopo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 24 publications
2
40
2
Order By: Relevance
“…Moderate exercise, in contrast to mild exercise, was found to be significant at reducing the high risk of being hypertensive among women in the semi-urban area. This finding is consistent with the results of previous studies conducted in South Africa and elsewhere [ 20 , 22 , 23 ], as they found that a lack of physical activity was significantly associated with hypertension. Some studies have shown that doing 30 min of physical activity five times per week reduces the risk of hypertension [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moderate exercise, in contrast to mild exercise, was found to be significant at reducing the high risk of being hypertensive among women in the semi-urban area. This finding is consistent with the results of previous studies conducted in South Africa and elsewhere [ 20 , 22 , 23 ], as they found that a lack of physical activity was significantly associated with hypertension. Some studies have shown that doing 30 min of physical activity five times per week reduces the risk of hypertension [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…South Africa has the highest prevalence of hypertension in Southern Africa [4]. Despite the high prevalence, the level of awareness and control of the disease is low among impoverished communities [3]. In the current study, the overall prevalence of uncontrolled hypertension was 56.83%.…”
Section: Discussionmentioning
confidence: 47%
“…In the year 2000, 972 million people were living with hypertension and a large burden was borne by economically disadvantage countries [2], where awareness and treatment often falls short. In South Africa, the prevalence of hypertension has been estimated at 27.4% for men and 26.1% for women [3], whereas an overall prevalence of up to 54% has been reported [4]. In the absence of effective intervention strategies to control this epidemic, the prevalence of hypertension is likely to increase in the next decade [2,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations